PENGARUH PENDIDIKAN & PELATIHAN (DIKLAT) DAN PENGALAMAN MENGAJAR TERHADAP PROFESIONALISME GURU SD NEGERI SE- KECAMATAN BATU HAMPAR KABUPATEN ROKAN HILIR - Hendri; Fadly Azhar; Isjoni (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article reports the effect of the variables of (1) education and training (DIKLAT) on teacher professionalism, (2) teaching experience on teacher professionalism, and (3) education and training (DIKLAT) and teaching experience mutually on teacher professionalism. The research respondents involved elementary school teachers in Batu Hampar District, Rokan Hilir. The sample was 62 teachers and was obtained by purposive sampling technique. Data were collected through the distribution of questionnaires and portfolios as the research instruments. The data analysis used was descriptive analysis, prerequisite analysis, and hypothesis testing. The instrument of coefficient reliability was calculated by using the Alpha Cronbach formula. The results showed that there was a positive effect between education training (DIKLAT) and teacher professionalism, which was 0.476, and there was a positive effect between teaching experience and teacher professionalism, which was 0.690. Meanwhile, the effect between education and training (DIKLAT) and teaching experience and teacher professionalism were simultaneously 0.766.